Studi Deskriptif mengenai Tipe Forgiveness pada Anggota Paduan Suara Mahasiswa Universitas âXâ di Kota Bandung - Samuel, Christian; Theresia, Ellen; Rahmani, Kristin (Zenit, 2015)
This research describe the type of forgiveness in the members of university student choir of „Xâ University in Bandung. The sample are selected by using the method of purposive sampling. There are 42 samples that participate in the research. The method of research used in this research is thedescriptive research method.To measure the primary data in the research, the Decisional Forgiveness Scale (DFS) and Emotional Forgiveness Scale (EFS) are used. Both scales were constructed by Worthington (2006)whose works have been translated into Bahasa Indonesia by Heliany Kiswantomo, M.Si., Psychologist. Meanwhile, the validity of the measuring tool utilizes the construct validity technique ofRank Spearman formula with the result 8 items are valid for the EFS and 7 items valid for the DFS with validity scale of each measuring tool in between 0,4-0,7. Furthermore, the reliability of the measuring tool is processed using alpha cronbach with the result of 0.567 for the DFS and 0.782 for the EFS.The results acquired based on the statistic data process are as follow: 38.1% respondents have high level in both DF (Decisional Fogiveness) and EF (Emotional Forgiveness) degrees and the 33.3% respondents have low level in both DF and EF degrees. In addition, 16.7% respondents have atype of forgiveness with a high DF degree and 11.9% respondents have a type of forgiveness with a high EF degree. There are also relations between the aspects of forgiveness traits, depth of hurt, frequency of hurtful events, attitude of the offender, empathy, and gender of the members of universitystudent choir of „Xâ University in Bandung with the forgiveness types. Based on this research, the researcher offers advices to other researchers who are interested to do research on the correlation between the factors affecting forgiveness types. Moreover, the research may also observe on the contribution of the environment in developing forgiveness in an individual.Keywords : forgiveness, type of forgiveness, members of university student choir